THE RELIABILITY OPERATING MODEL OF AIRLINE - Кучер, О.; Власенко, П. (Science-based technologies, 2010)
The reliability operating model of airline is considered. The Reliability control program of airline is proposed. The main systems of Reliability control program (data collection system, data analysis system, performance standards, corrective action system, presentation of data) are considered. The schema of aircraft, components and technical dispatch reliability definition process is proposed. The graphics and tables of aircraft and compo-nents reliability are shown